The image of presence and the presence of the image - Feinstein, K. * (Springer, 2020)
This article traces the development of art from the Renaissance to contemporary media practice. It looks at how images are made in relation to the main theoretical paradigm of the age. Moving from the window metaphor/Cartesian thought to media art/Ontology it focuses on how presence has been central to how we view and understand images and how they place us in the world. This paper develops the theoretical relationship of art practice based on presence as being central to how our identity is linked to our relationship to otherness through technology.